2019
DOI: 10.3389/fphar.2019.00405
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Protects Against MCD-Induced Development of NASH via Upregulating HSP72 and Downregulating mTOR in a Manner Distinctive From Metformin

Abstract: The present study investigated the effects of matrine on non-alcoholic steatohepatitis (NASH) in mice induced by a methionine choline-deficient (MCD) diet and the mechanism involved. The study was performed in C57B/6J mice fed a MCD diet for 6 weeks to induce NASH with or without the treatment of matrine (100 mg/kg/day in diet). Metformin was used (250 mg/kg/day in diet) as a comparator for mechanistic investigation. Administration of matrine significantly reduced MCD-induced elevations in plasma ALT and AST b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Previous studies demonstrated that another crucial participator in the progression of NASH is the network of pro‐inflammatory chemokines and cytokines 82,83 . Several inflammatory factors, such as TNF‐α, IL‐1β and IL‐6, have been proved to enable steatosis and liver damage, thus promoting the occurrence and progression of NASH 84,85 . In addition, TNF‐α was supposed to be a pivotal mediator of NASH development, 86 and inhibition of TNF‐α activity by anti‐inflammatory drugs ameliorated inflammation, liver damage and NASH 87 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that another crucial participator in the progression of NASH is the network of pro‐inflammatory chemokines and cytokines 82,83 . Several inflammatory factors, such as TNF‐α, IL‐1β and IL‐6, have been proved to enable steatosis and liver damage, thus promoting the occurrence and progression of NASH 84,85 . In addition, TNF‐α was supposed to be a pivotal mediator of NASH development, 86 and inhibition of TNF‐α activity by anti‐inflammatory drugs ameliorated inflammation, liver damage and NASH 87 .…”
Section: Discussionmentioning
confidence: 99%
“…82,83 Several inflammatory factors, such as TNF-α, IL-1β and IL-6, have been proved to enable steatosis and liver damage, thus promoting the occurrence and progression of NASH. 84,85 In addition, TNF-α was supposed to be a pivotal mediator of NASH development, 86 and inhibition of TNF-α activity by anti-inflammatory drugs ameliorated inflammation, liver damage and NASH. 87 Consistent with previous researches, mice fed a MCD diet effectively developed marked hepatic inflammation that simulated the natural development of NASH in human.…”
Section: Discussionmentioning
confidence: 99%
“…Various in vivo studies have demonstrated the role of alkaloids in treating fibrosis. In NASH mice fed an MCD diet, matrine decreases the expression of TGF-β, collagen Ⅰ, and Smad3 by inhibiting the NLRP3 inflammasome, at least partially (Mahzari et al, 2019). In CCl 4 -induced liver injury in rats, tetramethylpyrazine possesses an antifibrotic role in alleviating liver injury and fibrogenesis through the involvement of PDGF-βR/NLRP3 signaling pathway.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Decreased NOX4 activity and mitochondrial oxidative stress and inhibited protein kinase C α (PKC α ) activity, which accounted for the effect of metformin on Gal-3 expression, may be a consequence of increased levels of TSC2 phosphorylation and subsequent inactivation of the mTOR-S6K signaling pathway [ 29 ]. However, metformin treatment did not show any effects on methionine-choline-deficient- (MCD-) induced increases in mTOR activity or the NASH phenotype, such as inflammation and collagen deposition, in NASH mice [ 90 ].…”
Section: The Underlying Mechanisms Of Metformin In Antifibrosismentioning
confidence: 99%